Evaluation of the planting performance for planting substrate using the SQI-CRITIC combination model based on the least squares method - Wang, Ning; Xia, Dong; Duan, Xiaoming; Zhao, Bingqin; Xu, Wennian (Frontiers in Environmental Science, 2025)
BackgroundTo improve the scientificity of the evaluation results of the planting performance of the Yellow River sediment based on planting substrate.MethodsThis study replaced the natural soil with Yellow River sediment, used cement as the cementing material, added different proportions of organic matter and amendment of habitat material to prepare planting substrate based on the Yellow River sediment, and carried out experiments by using oats and proposed a combined SQI-CRITIC combined weighting calculation method based on the least square method for its evaluation.ResultsThe results showed that (1) different proportions of cement and amendment of habitat material led to significant variations in the planting performance of the planting substrate based on Yellow River sediment: among the 5# mix ratio, the plant height (12.5 cm) and biomass (3.06 g) of oats reached extreme values. Photosynthetic rate (1.97 μmol∙m−2∙s−1) and transpiration rate (0.25 mmol∙m−2∙s−1) were significantly higher than the other fitness ratio components (P < 0.05), while the stomatal width (87.03 μm) was the largest and stomatal density (19.6%) was the lowest (P < 0.05). (2) The results calculated by the SQI-CRITIC combination model based on the least square method are scientific and effective, more accurate and in line with the actual situation. (3) The comprehensive analysis recommended the use of a quality mix ratio (mixture of sediment, amendment of habitat material, organic matter, cement = 100:3:12:4) in ecological restoration to achieve the best plant growth and ecological restoration effect.ConclusionThe experimental results can be extended to more areas that need to use sandy soil for ecological restoration, with a view to providing a theoretical basis for soil quality evaluation, soil and water conservation control, and ecological construction in the Yellow River Basin.